Azaarenes: 13 rings in a row by cyclopentannulation [data] - Maier, Steffen (Universität, 2023)
Cyclopentannulation was explored as a strategy to access large, stable azaarenes. Buchwald-Hartwig coupling of previously reported di- and tetrabro...